An investigation of the fluids involved in the formation of some Irish lower carboniferous dolomites - Mulhall, Claire Marie (Trinity College (Dublin, Ireland). Department of Geology, 2004)
Irish Carboniferous rocks are host to an abnormally large amount of lead/zinc mineralisation and are internationally important in studies of the genesis of carbonate- hosted lead/zinc deposits. The host to mineralisation at Lisheen and Galmoy, the two most recently discovered commercial Zn-Pb deposits, is dolomitised late Toumaisian Waulsortian Limestone. This association between dolomite and base-metal sulphides has stimulated much research into the nature of the fluids responsible for the dolomitisation and the relation of dolomitisation to mineralisation. This study provides a more detailed examination of several dolomitised sections throughout the Irish Midlands, both within and outside the main mineralised zone, than carried out to date, in an effort to reconstruct their diagenetic and fluid flow history. Dolomitisation post-dated the final porosity occlusion within the precursor limestone in all of the areas studied. Fine-grained grey dolomite occurred during the initial stages of dolomitisation and commonly selectively replaced the micrite and bryozoan material. Replacement by this dolomite was generally mimetic. Texturally later coarse-grained white dolomite has a similar luminescence to the fine-grained dolomite and is both a replacive and open space-filling dolomite. Replacement by this dolomite is non-mimetic, with the dolomite crystals being orders of magnitude greater than the precursor calcite phase. At least during the initial stages of dolomitisation dissolution seams may have been exploited as conduits, enabling the Mg bearing fluids to move through the well-cemented limestone.
Keywords: Geology, Ph.D.; Ph.D. Trinity College Dublin